Subalternity and Linguistic Dispossession: On the Planning of the Galician-Portuguese in the Autonomous Galicia - Roberto Samartim (Cuadernos Europeos de Deusto, 2022)
We start from the centrality attributed in the analysis to the concept of subalternity (Gramsci), and we review the bibliography and the different positions related to the planning of the corpus, the status, and the acquisition of Galician in the autonomous period (1981-2021). After identifying the normative and ideological elements on which subalternity rests in each of these three areas of linguistic planning, we summarize the positions and programmatic proposals of the main groups that participate in the political-linguistic debate in autonomous Galicia. We review the legal-political framework enshrining the «subordinate co-officiality» (Carvalho Calero) and regulating the presence of Galician in compulsory education from the end of the Franco regime until decree 79/2010 currently in force. We synthesize the process of coding Galician in contemporary times in relation to the groups involved, the alleged coding criteria and the results regarding the relationship between Galician, Portuguese and Spanish. We confirm that the socialisation of linguistic and ideological materials subordinated to Spanish (also not referenced in the other Galician-Portuguese norms) means a break with the idea of a central language in the tradition of pre-autonomous Galicianism and minimises the impact of the linguistic interference of Spanish in Galician, at the same time that it does not provide sufficient materials to stop it and reverse it. We conclude that the idea of language and the autonomous legal-political framework enshrine subalternity and explain the progress of the linguistic-cultural interference and substitution process that leads to the linguistic dispossession that threatens the Galician community today.